ECHO : ethnographic, cultural and historical overview of Yukon's First Peoples - Castillo, Victoria Elena; Schreyer, Christine; Southwick, Tosh; University of British Columbia. Okanagan Campus. Institute for Community Engaged Research Press; BC Open Textbook Project; BCcampus (Institute for Community Engaged Research Press, University of British Columbia, Okanagan, 2020)
"Today, First Nations peoples living in Yukon, Canada are reviving and practicing their cultural traditions in exciting ways. At the same time, there has been an influx of newcomers to the territory who want to learn more about Yukon's Indigenous peoples and their cultures. With hundreds of references for those wanting to delve deeper into particular topics, ECHO is a handbook that provides the most current research pertaining to Yukon First Nations peoples. Topics include archaeology, ethnology, and lifeways, relationships with newcomers (in the past and currently), the arts, and modern-day land claims. The volume also includes interviews with research collaborators who discuss the importance of community-based research. Castillo, Schreyer, and Southwick's solidly researched handbook serves as an important tool, both for teachers and students, seeking accurate information pertaining to the Indigenous cultures of Yukon"--BCcampus website.
This work is licensed under the Creative Commons Attribution NonCommercial NoDerivatives CC-BY-NC-ND.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes bibliographical references.
Description based on online resource; title from pdf title page (viewed on August 5, 2020).
Keywords: Indigenous peoples -- Yukon -- Guidebooks; Ethnology -- Yukon; Native peoples -- Yukon -- Guidebooks; Yukon -- History; Yukon -- Research; Electronic books